Thermal physics games using wordwall - Md Rashid, Siti Nafisah; Jaafar, Nor Fadhlin; Mohd Rais, Nurul Rashidah Syuhada; Ab Rahman, Nur Fara Ellyana (2022)
Physics lecturers typically teach using the traditional method, in which they pose questions to the students in the class at each tutorial session and ask them to complete them in the allotted time. This method can cause students to become bored and disengaged in class. To address this issue, 39 pre-diploma in science students from groups PD0071A1 and PD0071B2 at UiTM Cawangan Negeri Sembilan, Kuala Pilah Campus were introduced to Wordwall, an online educational game. The activity consisted of a review of the topic thermal physics, with students required to answer 15 questions, with their scores displayed on the leaderboard after the session. The students' perceptions of their learning experience, motivation to learn Physics, and expectations were reflected by the ratings collected from their survey responses. According to the findings, 93.8% of students agreed that learning Physics through digital resources was interesting, and 81.3% preferred using Wordwall gamification tools in class over traditional methods. Furthermore, 75% of them agreed that using Wordwall as a teaching aid motivates them to understand the topic thermal physics and increases their engagement in the classroom since the implementation of open and distance (ODL) learning this semester. It makes the class more interactive and learning more enjoyable.